Development of incisional herniation after midline laparotomy. Issue 1 (10th May 2017) - Harlaar, J. J.; Deerenberg, E. B.; Dwarkasing, R. S.; Kamperman, A. M.; Kleinrensink, G. J.; Jeekel, J.; Lange, J. F.
Abstract: Background: Incisional herniation is a common complication after abdominal surgery associated with considerable morbidity. The aim of this study was to determine whether incisional hernia is an early complication, in order to understand better the aetiology of incisional hernia formation. Methods: This study involved the secondary analysis of a subset of patients included in a large RCT comparing small and large tissue bites (5 mm every 5 mm, or 1 cm every 1 cm) in patients scheduled to undergo elective abdominal surgery by midline laparotomy. The distance between the rectus abdominis muscles (RAM distance) was measured by standardized ultrasound imaging 1 month and 1 year after surgery. The relationship between the 1‐year incidence of incisional hernia and the RAM distance at 1 month was investigated. Results: Some 219 patients were investigated, 113 in the small‐bites and 106 in the large‐bites group. At 1 month after surgery the RAM distance was smaller for small bites than for large bites (mean(s.d.) 1·90(1·18) versus 2·39(1·34) cm respectively; P  = 0·005). At 1 year, patients with incisional hernia had a longer RAM distance at 1 month than those with no incisional hernia (mean(s.d.) 2·43(1·48) versus 2·03(1·19) cm respectively; relative risk 1·14, 95 per cent c.i. 1·03 to 1·26, P  = 0·015). Conclusion: A RAM distance greater than 2 cm at 1 month after midline laparotomy is associated with incisional hernia. Closure with small bites results in a smaller distance between the muscles. Abstract : This is an exploratory study of a RCT comparing small tissue bites with large tissue bites for midline laparotomy closure. The rectus abdominis muscle distance at 1 month was smaller after the small‐bites technique. A larger rectus abdominis muscle distance was related to later incisional hernia formation. Small bites technique recommended